The mechanisms of carnosic acid attenuates tumor necrosis factor‐α‐mediated inflammation and insulin resistance in 3T3‐L1 adipocytes. Issue 4 (11th November 2013) - Tsai, Chia‐Wen; Liu, Kai‐Li; Lin, Yu‐Ru; Kuo, Wen‐Cheng
<x xml:space="preserve">Abstract</x> Scope Insulin resistance has been linked to a low‐grade chronic inflammatory response. Carnosic acid (CA), which is found in rosemary, has been reported to have antioxidant, anti‐inflammation, and anti‐adipogenic properties. Here, we examined the effects of CA on inflammation and insulin resistance in 3T3‐L1 adipocytes treated with tumor necrosis factor‐α (TNF‐α). Methods and results CA attenuated the TNF‐α‐induced mRNA expression of inflammatory genes, including IL‐6 and monocyte chemoattractant protein‐1. CA also attenuated the TNF‐α‐mediated activation of extracellular signal‐regulated kinase, c‐Jun NH2‐terminal kinase, and c‐Jun; the phosphorylation of inhibitor‐κB (IκB) kinase (IKK)α/β, the phosphorylation and degradation of IκBα, the nuclear translocation of p65, and the DNA‐binding activity of NF‐κB and AP‐1. CA or PP242 (an mTOR inhibitor) suppressed the TNF‐α‐induced protein expression of mTOR, p70S6K, eIF4E, and IL‐6. Moreover, CA attenuated the TNF‐α‐mediated suppression of peroxisome proliferator‐activated receptor γ, adiponectin, and adipocyte protein 2. CA reversed the TNF‐α‐mediated suppression of insulin‐stimulated glucose uptake and the phosphorylation of Tyr632 insulin receptor substrate‐1 (IRS‐1), Akt, and FoxO1, but decreased the TNF‐α‐induced phosphorylation of Ser307 IRS‐1 and total FoxO1. Conclusion CA attenuates TNF‐α‐mediated inflammation via inhibition of NF‐κB and AP‐1 pathways and insulin resistance via Akt‐dependent FoxO1 signaling in 3T3‐L1 adipocytes.